Comparison of the effects of intraocular pressure with phacoemulsification and extracapsular cataract extraction methods in dogs with cataract - Mustafa Arıcan; Hanifi Erol; Kurtuluş Parlak; Ümit Kamış; Nuri Yavru (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to investigate the effects of intraocularpressure (IOP) in extracapsular extraction (ECCE) and phacoemulsification (PHACO) methods with or without intraocular lens (IOL) on dogs with cataract for a 28-day period. Materials and Methods: Twenty adult dogs of both sexes with cataracts, weighing between 10 to 30 kg and at different ages were used as materials. Cataracts were diagnosed by direct and indirect ophthalmoscopy, ultrasonographic examination and biomicroscopy. Cataracts were classified as immature (7 animals), mature (7 animals) and hypermature (6 animals). Dogs were divided into two groups each consisting of 10 animals. Ten dogs with cataract were operated on for ECCE and the other group of 10 dogs underwent a phacoemulsification procedure. In the two groups, 10 animals were used for 41 dioptry single-piece acrylic intraocular lens. Results: Intraocular pressure was felt at the lowest level 14 days after the operation in the ECCE without IOL implanted group. The IOL implanted group showed irregular levels. Intraocular pressure level was the lowest on the 21st day, without IOL implanted group in phacoemulsification. However, all values remained within the reference values at the end of a 28-day period postoperatively. Conclusions: Both surgeries could be used for cataract cases in terms of IOP effects. Selection of the patient, correct surgical technique and adequate equipment are important for the success of a surgery. But, it has been also concluded that success of phacofragmentation surgery increased when the animals are in immature stages.